LEGAL CONSULTING IN INTERNET FORUMS: TRANSFORMATION OF LEGAL DISCOURSE IN EVERYDAY LANGUAGE - KUZNETSOVA, Natalia (Comparative Legilinguistics, 2011)
The author having examined the contents of several internet-forums tackles major means of legal discourse transformation in inter-personal communication, linking them with the peculiarities of mundane thinking and with characteristics of the categories “the addresser” and “the addressee”. Two basic vectors: subjectivity and concretization are regarded as most important in the adaptation of legal discourse for the demands of everyday life. Subjectivity is revealed in the presentation of a “me-focus” and “you-focus”, in the substitution of legal and special terms, bookish phrases by their substandard equivalents, as well as the usage of words with evaluative connotations to describe situations both in the whole and in the particular. Concretization is revealed in ascribing personal features to legal bodies and in the descriptive nominations of legal bodies by the means of spatial indexes.